Biological Investigations of Ru(II) Complexes with Diverse β‐Diketone Ligands. Issue 35 (6th August 2021) - Ryan, Raphael T.; Havrylyuk, Dmytro; Stevens, Kimberly C.; Moore, L. Henry; Parkin, Sean; Blackburn, Jessica S.; Heidary, David K.; Selegue, John P.; Glazer, Edith C.
Abstract: The β‐diketone scaffold is a commonly used synthetic intermediate, and is a functional group found in natural products such as curcuminoids. This core structure can also act as a chelating ligand for a variety of metals. In order to assess the potential of this scaffold for medicinal inorganic chemistry, seven different κ 2 ‐O, O'‐chelating ligands were used to construct Ru(II) complexes with polypyridyl co‐ligands, and their biological activity was evaluated. The complexes demonstrated promising structure‐dependent cytotoxicity. Three complexes maintained high activity in a tumor spheroid model, and all complexes demonstrated low in vivo toxicity in a zebrafish model. From this series, the best compound exhibited a ∼30‐fold window between cytotoxicity in a 3‐D tumor spheroid model and potential in vivo toxicity. These results suggest that κ 2 ‐O, O'‐ligands can be incorporated into Ru(II)‐polypyridyl complexes to create favorable candidates for future drug development. Abstract : Diketonate compounds can serve as ligands for metal complexes. Seven new complexes were generated to establish structure‐activity relationships for Ru(II) polypyridyl complexes containing a single diketonate ligand. While there is limited correlation between physiochemical property and biological activity, the series resulted in the identification of a new lead compound with high potency in 2D and 3D cancer models and low toxicity in zebrafish.